Interval Outcomes of a Lifestyle Weight-Loss Intervention in Early Adolescence - Christina Wei; Toby Candler; Elizabeth Crowne; Julian P. Hamilton-Shield (MDPI AG, 2018)
We undertook a feasibility study to reassess metabolic outcomes in young people with early onset obesity who attended a hospital-based lifestyle weight-loss intervention during adolescence. Comparisons of metabolic assessments, including body mass index standard deviation scores (BMI–SDSs), blood pressure (BP), oral glucose tolerance tests (OGTTs), lipid profile, and alanine transaminase (ALT), before and after treatment were made. Twenty-five subjects (10 males) with median ages (interquartile range, IQR) of 14.5 (12.6–15.4) years at the beginning of intervention and 18.2 (17.2–18.9) years at reassessment and who were 3.5 (2.4–6.5) years post-intervention were recruited. Twenty-eight percent had a ≥0.25 reduction in BMI–SDS from baseline (responders). Responders demonstrated significantly lower BMI–SDS, systolic BP, and glucose disposal at reassessment compared with baseline. They also showed significantly lower total fat percentage SDSs, trunk fat percentages, 120 min insulin, and ALT, as well as higher insulin sensitivity index (ISIcomp) than non-responders. Male gender and younger age at the initiation of intervention showed a non-significant trend towards greater success in weight loss. Long-term benefits were demonstrated in around one-quarter of obese adolescents after lifestyle modification treatment, with associated improvements in body composition and metabolic parameters.